Producing Altered States of Consciousness, Reducing Substance Misuse: A Review of Psychedelic-Assisted Psychotherapy, Transcendental Meditation and Hypnotherapy - Agnieszka D. Sekula; Prashanth Puspanathan; Luke Downey; Paul Liknaitzky (MDPI AG, 2024)
A set of interventions that can produce altered states of consciousness (ASC) have shown utility in the treatment of substance misuse. In this review, we examine addiction-related outcomes associated with three common interventions that produce ASCs: psychedelic-assisted psychotherapy (PP), Transcendental Meditation (TM) and hypnotherapy (HT). While procedurally distinct, all three interventions are associated with some common phenomenological, psychological, and neurobiological features, indicating some possible convergent mechanisms of action. Along with addiction and mental health outcomes, these common features are reviewed, and their impact on substance misuse is discussed. While our review highlights some mixed findings and methodological issues, results indicate that PP and TM are associated with significant improvements in substance misuse, alongside improvements in emotional, cognitive and social functioning, behavior-change motivation, sense of self-identity, and meaning. In contrast, and despite its broader acceptance, HT has been associated with mixed and minimal results with respect to substance misuse treatment. Authors identify key research gaps in the role of ASC interventions in addiction and outline a set of promising future research directions.